Programming Industrial Robots in the Fanuc ROBOGUIDE Environment - Boryan Vladimirov; Stiliyan Nikolov; Stanislav Tsolov (Engineering Proceedings)
Descriptions of the main CARC environments for programming industrial robots are given, describing the main used programming environments for various robot manufacturers such as ROBOGUIDE developed by FANUC Robotics, KUKA Sim and Kuka Work Visual developed by KUKA ROBOTICS, Robot Studio developed by ABB Robotics, K-ROSET and K-ROSET LITE developed by Kawasaki Robotics, Visual Component, DELMIA ROBOTICS of Dassault Systems, Tecnomatix Robotics & Automation Simulation of SIEMENS PLM Software/Simatic Robot Integrator, Visual Components, etc. A methodology describing the main stages, when working with computer systems, of off-line programming of industrial robots is proposed. The features characterizing the implementation of the stages defined in the methodology have been specified. The created methodology has been applied when working with the Fanuc ROBOGUIDE computer system. When using the given example of the Fanuc ROBOGUIDE, the emphasis is also on expanding the working space of the robot (Robot Envelope) by adding a 7th axis. The general software options that are added when performing this task are described, and two sample programs are given for the implementation of the given example—and a 3D simulation is made for moving a part (box). A control program has been generated for an industrial robot Fanuc LR Mate 200 iD/7L that shall perform “Pick and Place” operations and shall service a conveyor for the transportation of cartons and their arrangement on pallets.